Antiinflammatory and Antipyretic Activities of Stem Extract and Fractions of Telfairia occidentalis in Rodents - Okokon, Jude E; Osigwe, Chinyelu C.; Florence, Uwaeme Ugonma; Andrew, Ukeme Essien (Biology, Medicine, & Natural Product Chemistry, 2025)
Telfairia occidentalis Hook (Family-Cucurbitaceae) is a vegetable employed in Ibibio traditional medicine for the treatment of various diseases such as malaria and fever among others. The stem extract of Telfairia occidentalis was investigated for antiinflammatory and antipyretic activities in rodents using various experimental models.The stem extract (200 –600 mg/kg) of T. occidentalis was investigated for antiinflammatory activity against carrageenin, egg albumin and xylene – induced edema models and antipyretic activity against D-amphetamine, 2,4-dinitrophenol and yeast-induced pyrexia models.  The extract caused a significant (p<0.05 – 0.001) dose-dependent reduction of inflammation caused by different phlogistic agents used. These effects were comparable to those of the standard drug, (ASA, 100 mg/kg) used in some cases. The extract also exerted prominent inhibition of pyrexia on amphetamine and dinitrophenol-induced pyrexia (5 h). Inhibition was significant (p<0.05–0.001) from 3 to 5 h post- administration of extract and in a dose-dependent fashion. However, the stem extract did not affect yeast-induced pyrexia in mice. The anti-inflammatory and antipyretic effects of this plant may in part be mediated through the chemical constituents of the plant. The findings of this work confirm the ethnomedical uses of this plant to treat inflammatory and febrile conditions.